Entry deregulation, firm organization and wage inequality - Cooke, Dudley (2020)
This paper identifies a causal link between changes in product market competition, firm reorganization and within-firm wage inequality. We exploit a unique episode of comprehensive firm entry deregulation as a quasi-natural experiment and use exceptionally detailed linked employer-employee data for the universe of private sector firms and workers. We find that following deregulation affected firms flatten their hierarchies: the number of layers is reduced and managers´spans of control increased. Dropping a hierarchy layer is accompanied by a significant reduction in wage inequality within the firm, by 10% for the average pay ratio between the top and the bottom layer, showing that there are real changes arising from firm reorganization. Overall dispersion is also reduced. We discuss mechanisms and interpretations for these changes.